Smallholder value chains as complex adaptive systems: a conceptual framework - Orr, A.; Donovan, J.; Stoian, D. (International Crops Research Institute for the Semi-Arid Tropics, 2015)
Conventional analyses of value chains involving smallholders and the design of interventions that seek to strengthen their role in them often fail to account for important features of value chain performance. Markets, institutional frameworks and business relationships are dynamic, and value chain performance varies accordingly. Shocks and sudden changes occur frequently and require successful adaptation. This paper develops an expanded conceptual framework to understand value chain performance based on the theory of complex adaptive systems. The framework combines seven common properties of complex systems: time, uncertainty, sensitivity to initial conditions, endogenous shocks, sudden change, interacting agents and adaptation. We outline how the framework can be used to ask new research questions, analyse case studies, and develop new tools to increase the ability for enhanced risk management and adaptation.